Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-40875-1
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling RNA dynamical behavior of TPP riboswitches: a comparison between Escherichia coli and Arabidopsis thaliana

Abstract: Riboswitches are RNA sensors that affect post-transcriptional processes through their ability to bind to small molecules. Thiamine pyrophosphate (TPP) riboswitch class is the most widespread riboswitch occurring in all three domains of life. Even though it controls different genes involved in the synthesis or transport of thiamine and its phosphorylated derivatives in bacteria, archaea, fungi, and plants, the TPP aptamer has a conserved structure. In this study, we aimed at understanding differences in the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…They are extensively studied in prokaryotic cells due to their high abundance and outstanding contribution to directing transcription and translation in various metabolic, physiological, and pathological pathways [ 45 ]. The only known class of eukaryotic riboswitches found in fungi, archaea and plants resides within intronic regions of TPP metabolism genes and fine-tunes their AS and expression in response to TPP binding ( Figure 1 c) [ 52 , 152 , 153 , 154 , 155 , 156 ].…”
Section: Cellular Modulators Of Rna Structurementioning
confidence: 99%
“…They are extensively studied in prokaryotic cells due to their high abundance and outstanding contribution to directing transcription and translation in various metabolic, physiological, and pathological pathways [ 45 ]. The only known class of eukaryotic riboswitches found in fungi, archaea and plants resides within intronic regions of TPP metabolism genes and fine-tunes their AS and expression in response to TPP binding ( Figure 1 c) [ 52 , 152 , 153 , 154 , 155 , 156 ].…”
Section: Cellular Modulators Of Rna Structurementioning
confidence: 99%
“…Therefore, we wondered whether an integrated analysis of overall network properties (eg, node centralities) in the context of the suboptimal paths would enable a deeper understanding of allostery in catK. A recent study revealed that the distributions of centralities obtained from communicating paths differ from those extracted from the overall network 71 . However, no attempt was made to compare the distributions of centralities obtained from other paths exhibiting similar lengths.…”
Section: Discussionmentioning
confidence: 99%
“…those extracted from the overall network. 71 However, no attempt was made to compare the distributions of centralities obtained from other paths exhibiting similar lengths. To overcome this bias, we designed a protocol to compare critical residues from allosteric sites with a decoy set composed of residues equally distant from the sink node (Figure 1).…”
Section: Searching For Other Catk Pockets Displaying Allosteric Potmentioning
confidence: 99%
“…They act in the recognition and post-transcriptional regulation of specific metabolites, controlling the expression of genes related to their respective ligands’ synthesis and transport [ 1 , 3 , 4 ]. A riboswitch recognizes a particular metabolite and is responsible for gene regulation [ 5 , 6 ]. In addition, most of the riboswitches work by negative feedback, and their respective metabolites are sometimes essential for the organism’s maintenance [ 3 , 6–8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, over 40 riboswitches have been identified in bacteria, although the thiamine pyrophosphate (TPP) riboswitch stands out as the only class identified so far for eukaryotic organisms [ 5 , 6 , 13 , 14 ]. The TPP riboswitch recognizes the metabolite and regulates biosynthesis or transport of TPP (or its precursors) in a wide variety of organisms distributed among the three domains of life [ 5 , 10 , 14 ]. The metabolite TPP is a bioactive derivative of thiamine, composed of two moieties synthesized independently: thiazole (THZ) and pyrimidine (HMP) [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%